Dendritic fibromyxolipoma in the right inguinal and perineum regions: a case report and review of the literature - Zhang, Xing Jian (BioMed Central, 2013)
ABSTRACT: A 32-year-old woman presented with a slow-growing, painless, subcutaneous lesion in the right inguinal and perineum regions. The mass was 24.0 cm × 10.5 cm × 5.0 cm in size, well circumscribed, mobile, and rubbery. Microscopically, the resected mass was mainly composed by a proliferation of small spindle or stellate cells, variably admixed with mature adipose tissue, embedded within an abundant myxoid and collagenized stroma. Immunohistochemically, the spindle and stellate cells were strongly positive for vimentin, CD34, and bcl-2 antibodies but not for smooth muscle actin and desmin. The tumor was diagnosed as dendritic fibromyxolipoma based on the typical findings of histology and immunohistochemistry. Clinical follow-up of 9 months after surgery revealed no evidence of recurrence. We report the first case of dendritic fibromyxolipoma in the right inguinal and perineum regions and discuss the different diagnosis. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1313680868103019.